Gingival Margins' Modifications during Orthodontic Treatment with Invisalign First®: A Preliminary Study - Roberta Lione; Francesca Gazzani; Sofia Moretti; Carlotta Danesi; Elisabetta Cretella Lombardo; Chiara Pavoni (MDPI AG, 2022)
The aim of the study was to assess modifications of gingival morphology at the end of Phase I treatment with Invisalign First. Eighteen subjects (ten females, eight males, mean age nine years) treated with Invisalign First were selected. The following parameters were measured on intraoral photographs before treatment (T0) and after the first set of aligners (T1) at level of permanent incisors, deciduous canines and molars: gingival margin height (GMH) and deciduous canine inclination (DCI). A paired t-test was used to evaluate T1-T0 changes. The level of significance was established at 5%. Deciduous canines' GMH showed a major reduction between T1 and T0 accounting for 0.87 mm and 0.86 mm, respectively on the right and left sides. DCI increased for all patients in the interval T0-T1 on both sides, +7.11° on the right and +7.5° on the left. Tooth movement during Invisalign First induced significant modifications of gingival contour resulting in a more harmonious smile.